Biological samples for examination: concepts, conditions, sampling tactics - M. H. Shcherbakovskyi; A. M. Protsenko; A. E. Volkova (Bulletin of Kharkiv National University of Internal Affairs)
During the commission of crimes, traces of biological origin are left on the objects of the environment, tools, clothing, and the body of the participants. To conduct an identification study, an expert needs to compare the traces of the crime with biological samples of the person being tested. Criteria for determining biological samples are proposed. The biological criterion means that the samples reflect the internal and external properties of a person as a biological organism. The informational criterion is that the samples meet certain requirements: undoubted origin, required quantity, proper quality, compatibility with traces of crime. The identification criterion establishes that the human properties reflected by the samples are individual, stable, cannot be deliberately altered by a person and are suitable for identification. The procedural criterion means that biological samples must be collected in a lawful manner. Based on these criteria, biological samples for examination include: body parts; secretions as products of human activity; imprints of the skin relief of the human body.